Correlation between self-esteem, level of identification with parents, and adjustment of parents and children - Stanford, George H.; Pedersen, Darhl M. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Correlations were obtained between self-esteem in children and: parental adjustment scores on the California Test of Personality (CTP), and identification with parents. Correlations were also obtained between children’s CTP scores and: self-esteem, parental CTP scores, and identification with parents. No systematic relationships were found between self-esteem and: parental CTP scores, or identification with parents. However, the self-esteem of girls was significantly correlated with the social adjustment of their fathers. Selfesteem as significantly correlated with adjustment in boys, but not girls.